Dynamic Colonization of Klebsiella pneumoniae Isolates in Gastrointestinal Tract of Intensive Care Patients - Sun, Qiao-ling; Gu, Danxia; Wang, Qi; Hu, Yanyan; Shu, Lingbin; Hu, Jie; Zhang, Rong; Chen, Gong-Xiang (Frontiers in Microbiology, 2019)
Gastrointestinal carriage is regarded as a major reservoir of K. pneumoniae infections, especially in intensive care patients. A total of 101 (95.3%) KPC-producing carbapenem-resistant K. pneumoniae (CRKP) isolates were identified among 106 CRKP isolates collected from stool samples of inpatients performing active rectal screening for CRE during hospitalization in the ICUs of a tertiary hospital between 2016 and 2017. Among them, six KPC-producing CRKP isolates from three patients (two isolates for each patient) were identified with distinct antibacterial susceptibility. Our findings showed that: (1) blaKPC-2 gene is predominant in CRKP strains isolated from the intensive care patients and can be incorporated into various plasmids that are transmissible among multiple bacterial hosts in the human gastrointestinal tract; (2) the human gastrointestinal tract has a capacity to dynamically colonize multiple clones of CRKP strains with varied plasmids, diverse antimicrobial resistance genes and virulence genes. K. pneumoniae colonization is an important step in progression to extraintestinal infection, which provides the rationale for establishing intervention measures to prevent subsequent infection. Thus, close surveillance on CRKP colonization, together with effective infection prevention and control measures, should be put into practice.